2021
DOI: 10.1038/s41420-021-00577-y
|View full text |Cite|
|
Sign up to set email alerts
|

CircPVT1 promotes gallbladder cancer growth by sponging miR-339-3p and regulates MCL-1 expression

Abstract: Circular RNAs (circRNAs) have been implicated in modulating biological processes in some tumors. However, the contributions and molecular mechanisms of circRNAs to gallbladder cancer (GBC) remain largely unknown. In the present study, our results showed circPVT1 expression was significantly upregulated in GBC tissues and cells. Higher circPVT1 expression was correlated with lymph node metastasis, advanced TNM stage, and poor overall survival (OS) in patients with GBC. Subsequently, knockdown of circPVT1 signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, some studies have reported that circPVT1 promotes the proliferation of other cancers, including lung cancer, [16][17][18] thyroid cancer, 19,20 and gallbladder cancer. 21 These suggest the dual role of circPVT1 in cancer development, either as a driver or a suppressor. Many miRNAs can be targeted by circPVT1, such as miR-30e, 22 miR-21-5p, 23 miR-429.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have reported that circPVT1 promotes the proliferation of other cancers, including lung cancer, [16][17][18] thyroid cancer, 19,20 and gallbladder cancer. 21 These suggest the dual role of circPVT1 in cancer development, either as a driver or a suppressor. Many miRNAs can be targeted by circPVT1, such as miR-30e, 22 miR-21-5p, 23 miR-429.…”
Section: Discussionmentioning
confidence: 99%
“… 24 In osteosarcoma, miR-339-3p is sponged by CircDOCK1 and blunts the sensitivity of osteosarcoma cells to cisplatin. 13 Therefore, miR-339-3p may inhibit cancer tumors. Consistently, we found that the miR-339-3p inhibitor stimulated the migration and proliferation of osteosarcoma cells.…”
Section: Discussionmentioning
confidence: 99%
“… 12 MiR-339-3p has been well documented as a tumor suppressor in various cancers, such as osteosarcoma. 13–15 However, the regulatory mechanisms of circ_0020378 are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Circ_PVT1 is involved in the regulation of a variety of cellular events. Circ_PVT1 overexpression increases the invasive capacity of esophageal and gallbladder cancer cells [66,67]. In addition, circ_PVT1 makes lung cancer cells less responsive to Pemetrexed and cisplatin by elevating the expression of ABCC1 (also known as multidrug resistance-associated protein 1, MRP1) [68].…”
Section: Gastric Cancer 231 Circ_0032821 Circ_prrx1 and Circ_pvt1mentioning
confidence: 99%